2020
DOI: 10.1017/s0033291720005188
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy in the UK: the Oxford coronavirus explanations, attitudes, and narratives survey (Oceans) II

Abstract: Background Our aim was to estimate provisional willingness to receive a coronavirus 2019 (COVID-19) vaccine, identify predictive socio-demographic factors, and, principally, determine potential causes in order to guide information provision. Methods A non-probability online survey was conducted (24th September−17th October 2020) with 5,114 UK adults, quota sampled to match the population for age, gender, ethnicity, income, and region. The Oxford COVID-19 vaccine hesitancy scale assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

86
699
20
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 653 publications
(913 citation statements)
references
References 40 publications
86
699
20
7
Order By: Relevance
“…Stratified per country, a total of 60 surveys were found with the largest sample size (n = 5114) in the study conducted in the UK by Freeman et al, while the smallest sample size (n = 123) was found in the study conducted in Malta by Gretch et al, among general practitioners and trainees [48,49]. Out of these 60 surveys, 47 were among the general public, eight surveys were among healthcare workers (doctors, nurses, or others), three surveys were among parents/guardians and two surveys involved University students ( Table 1).…”
Section: Characteristics Of the Papers Included In This Reviewmentioning
confidence: 94%
“…Stratified per country, a total of 60 surveys were found with the largest sample size (n = 5114) in the study conducted in the UK by Freeman et al, while the smallest sample size (n = 123) was found in the study conducted in Malta by Gretch et al, among general practitioners and trainees [48,49]. Out of these 60 surveys, 47 were among the general public, eight surveys were among healthcare workers (doctors, nurses, or others), three surveys were among parents/guardians and two surveys involved University students ( Table 1).…”
Section: Characteristics Of the Papers Included In This Reviewmentioning
confidence: 94%
“…Second, it is currently unclear that transparent communication of information would necessarily affect vaccination rates in any predictable way. On the one hand, explaining the results of clinical trials and the regulatory procedures in place may serve to alleviate concerns over vaccine efficacy and safety and ultimately increase intention to vaccinate as suggested by some researchers (Freeman et al, 2021). On the other, as noted by Petersen et al (2020), it is also possible that individuals may find the information more concerning, increasing their perception of vaccines as relatively more dangerous or ineffective.…”
Section: Transparent Communication Of Vaccine Risks and Benefitsmentioning
confidence: 99%
“…Numerous cross-sectional surveys around the world have identified perceptions of vaccines as safe and effective as key predictors of COVID-19 vaccination intentions (e.g. Callaghan et al, 2021;Freeman et al, 2021;Karlsson et al, 2021;Y. Lin et al, 2020;Paul et al, 2021;Wang et al, 2021;Wong et al, 2020).…”
Section: Beliefs About Covid Vaccines and Vaccine Hesitancymentioning
confidence: 99%
See 2 more Smart Citations